Optical ceramics and crystals in laser and optical applications - Koh, Kian Seng (2014)
Diamond, emerald, ruby and jade are only a few samples of ceramic gems and jewels. Electronic ceramics have conduction behaviors from insulators, to semiconductors, to metallic conductors, to superconductors, and ionic conductors; and have many other very attractive properties such as opto-electrical property, thermoelectricity, ferroelectricity, piezoelectricity, magnetic property, electrochemistry, etc. They have been widely used as sensors, actuators, transducers, and many electronics devices such as high temperature heating elements, varistors, solid fast-ion conductor battery, fuel-cells, humidity detectors, gas sensors by nano-particles, capacitors, gate dielectrics of SiO2 and high-k optical switch and information storage, microwave filters, etc.